Takdir Alisjahbana dan Pemikiran Kebudayaan - Abdul Hadi W.M. (Refleksi: Jurnal Kajian Agama dan Filsafat, 2006)
This essay will attempt to discuss specific aspects of cultural thought by Sutan Takdir Alisjahbana (STA), especially those related to values. However, before delving into STA’s cultural thought, the definition of culture as it developed up to the early 20th century CE, particularly within the intellectual traditions of Islam and the West, will be presented. Towards the end of this essay, a comparison will be drawn between STA’s thoughts and those of Yukichi Fukuzawa, a Japanese civilization expert who lived from the mid-19th to the early 20th century CE, whose ideas influenced the direction of Japanese modernism in various fields.